Mangrove Ecosystem Services, Associated Threats and Implications for Wellbeing in the Mono Transboundary Biosphere Reserve (Togo-Benin),West-Africa - GNANSOUNOU, Sètondé Constant; SALAKO, Kolawolé Valère; Sagoe, Alberta Ama; Mattah, Precious Agbeko Dzorgbe; Aheto, Denis Worlanyo; Glèlè kakaï, Romain (My University, 2022)
Mangroves are important coastal ecosystems, which deliver diverse and crucial services to humans. This study explored the diversity of mangrove ecosystem services, their associated threats as well as their contribution to livelihoods and wellbeing of coastal communities in the Mono Transboundary Biosphere Reserve (MTBR) located between Benin and Togo. Data were collected using the exploratory sequential mixed method. The approach included field reconnaissance, focus group discussions (n = 14), in-depth interviews (n = 17), household survey (n = 274) and direct observations. A total of 21 services and 7 associated threats were recorded in the entire reserve. Provisioning services were the most important service for mangroves in the reserve followed by supporting services, regulating services and cultural services. Change in water salinity, mangrove overharvesting and illegal, unreported and unregulated fishing were the three major threats to mangrove ecosystem services in the reserve. Most of the respondents indicated that the current flow of provisioning services, regulating services and cultural services does not sustain their wellbeing and livelihoods. However, the perception varied significantly across respondents’ gender, ethnical groups, educational background and country. Our study showed some similarities between the two countries but also highlighted important differences which can assist the sustainable management of mangroves in the MTBR.
Keywords: wellbeing; mangroves; ecosystem services; mono transboundary biosphere reserve; West-Africa